2006
DOI: 10.1158/1078-0432.ccr-06-0799
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-Suppressing Potential of Ribonucleotide Reductase Small Subunit p53R2 in Human Cancer Cells

Abstract: Purpose: Previous gene transfection studies have shown that the accumulation of human ribonucleotide reductase small subunit M2 (hRRM2) enhances cellular transformation, tumorigenesis, and malignancy potential. The latest identified small subunit p53R2 has 80% homology to hRRM2. Here, we investigate the role of p53R2 in cancer invasion and metastasis. Experimental Design: The immunohistochemistry was conducted on a tissue array including 49 primary and 59 metastatic colon adenocarcinoma samples to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…In previous studies, we have extensively investigated the functional and structural regulation of RR subunits including RRM1, RRM2, and RRM2B (also known as p53R2) [2-9]. RRM2B has been demonstrated to be a p53-inducible RR subunit that functions in cell cycle regulation, DNA repair, mitochondrial homeostasis, and the suppression of metastasis [3, 10-14]. Mutation of the RRM2B gene causes severe mitochondrial DNA (mtDNA) depletion, which indicates that RRM2B plays a crucial role in the supply of dNTPs used for mtDNA synthesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we have extensively investigated the functional and structural regulation of RR subunits including RRM1, RRM2, and RRM2B (also known as p53R2) [2-9]. RRM2B has been demonstrated to be a p53-inducible RR subunit that functions in cell cycle regulation, DNA repair, mitochondrial homeostasis, and the suppression of metastasis [3, 10-14]. Mutation of the RRM2B gene causes severe mitochondrial DNA (mtDNA) depletion, which indicates that RRM2B plays a crucial role in the supply of dNTPs used for mtDNA synthesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The invasion-suppressing ability of p53R2 was also found in oropharyngeal, prostate, pancreatic and colon cancer cell lines (15,16). In addition, these authors determined that the invasion-suppressing ability of p53R2 was not related to RR enzymatic activity (10). Plao et al concluded that p53R2 negatively modulates serum-induced MEK-ERK activity and inhibits the MEK-ERK-mediated malignancy potential to suppress invasion of human lung cancer cells (8).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study concluded that the overexpression of RRM2 and p53R2, but not RRM1, in mice specifically induces lung neoplasms (12). p53R2 was also found to contain a malignancy-suppressing activity (10). The role of p53R2 expression in tumor formation has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of p53R2 is associated with clinical response in myelodysplatic syndrome/acute myelogenous leukemia [25]. It has been suggested that the opposite regulation of hRRM2 and p53R2 in the invasion potential may play a critical role in determining the invasion and metastasis phenotype in cancer cells [26].…”
Section: Introductionmentioning
confidence: 99%